Brain Stimulation Therapy for Central Post-Stroke Pain from a Perspective of Interhemispheric Neural Network Remodeling - Morishita, Takashi; Inoue, Tooru (Frontiers in Human Neuroscience, 2016)
Central post-stroke pain (CPSP) is a debilitating, severe disorder affecting patient quality of life. Since CPSP is refractory to medication, various treatment modalities have been tried with marginal results. Following the first report of epidural motor cortex stimulation (MCS) for CPSP, many researchers have investigated the mechanisms of electrical stimulation of the motor cortex. CPSP is currently considered to be a maladapted network reorganization problem following stroke, and recent studies have revealed that the activities of the impaired hemisphere after stroke may be inhibited by the contralesional hemisphere. Even though this interhemispheric inhibition (IHI) theory was originally proposed to explain the motor recovery process in stroke patients, we considered that IHI may also contribute to the CPSP mechanism. Based on the IHI theory and the fact that electrical stimulation of the motor cortex suppresses CPSP, we hypothesized that the inhibitory signals from the contralesional hemisphere may suppress the activities of the motor cortex in the ipsilesional hemisphere, and therefore pain suppression mechanisms may be malfunctioning in CPSP patients. In this context, transcranial direct current stimulation (tDCS) was considered to be a reasonable procedure to address the interhemispheric imbalance, as the bilateral motor cortex can be simultaneously stimulated using an anode (excitatory) and cathode (inhibitory). In this paper, we review the potential mechanisms and propose a new model of CPSP. We also report two cases where CPSP was addressed with transcranial direct current stimulation (tDCS), discuss the potential roles of tDCS in the treatment of CPSP, and make recommendations for future studies.